Number 1: Chronic Obstructive Pulmonary Disease - Norman L Jones (Canadian Respiratory Journal)
With the editorial staff of the Canadian Respiratory Journal, I extend our best wishes for the New Year, and heartfelt thanks to everyone who has helped the Journal establish itself in the competitive field of quality, peerreviewed publications in chest medicine. It may seem odd to start the new millennium with an editorial eulogizing the past, but even in these "postmodern" days of chaos, complexity and ordered unpredictability, the past can be seen to have a huge influence on the present and the future. The importance of looking back on work that has influenced our present views on chest medicine, and why, was the main reason for the series inaugurated in the present issue - "Modern Classics Revisited" (pages 71-76).